Are Citizens Ready for Active Climate Engagement or Stuck in a Game of Blame? Local Perceptions of Climate Action and Citizen Participation in Chilean Patagonia - Sapiains, Rodolfo; Azocar, Gabriela; Moraga, Pilar; Valenzuela, Catalina; Aldunce, Paulina; Cornejo, Camilo; Rojas, Maisa; Pulgar, Antonio; Medina, Loreto; Bozkurt, Deniz (My University, 2022)
Deep structural transformations aimed at strengthening climate action and community participation are occurring in Chile, especially after the social unrest of October 2019. The ongoing political crisis has even generated the unprecedented possibility of writing a new constitution through an entirely democratic process. This article explores to what extent these structural transformations are also associated with cognitive and relational changes in the population, especially in terms of community participation. An online survey (n = 1.117) was applied to people over 18 years old in Punta Arenas in November 2020. This is the southernmost city of the American continent, one of the areas most affected by climate change, highly isolated from the rest of the country, and with a strong regional ecological identity. Results show that climate change is perceived as the main environmental problem affecting the city, with multiple negative consequences, but also with some potentially positive impacts. At the same time, environmental and constitutional expectations suggest the state of the environment is deemed to be critical for the future of the city. However, a traditional top-down understanding of community participation still prevails as most participants perceive the citizens' role in dealing with environmental issues as limited to individual, passive, and reactive actions, or reduced to being responsible consumers. These results show that transforming institutions, rules and regulations alone does not guarantee a broader engagement of local communities in more ambitious, committed, and lasting climate action, even with a high climate change concern in the population. Creating strategies aimed at more profound cognitive and relational changes from a bottom-up perspective will also be necessary to avoid negative transformation trajectories.
Keywords: climate change; transformation; chile; constitution; community participation